National Citation Index of National Articles and Models and Methods for Creating a Bibliographic Electronic Platform of Scientific Publications - Nazirova Elmira Shodmonovna; Hojiev Suhrob Amandullo o‘g‘li (Periodica Journal, 2022)
Currently, one of the important tasks is the development of scientific activity in various fields, the publication of scientific results written by scientists, scientific researchers in prestigious scientific journals, increasing their scientific performance on international platforms (h-index). Based on this task, the results of scientific research carried out by scientists on international platforms are now published and their analysis processes are carried out effectively by international scientists
Keywords: effectively; carried; processes; scientists